Influence of factors of solar and geomagnetic activity on development of spontaneous 82 labor activity - E. V. Osipova; A. S. Averina; V. V. Sukhovskaya; N. V. Protopopova; A. A. Bazhenov; E. B. Druzhinina; A. V. Labygina; M. A. Darenskaya (Acta Biomedica Scientifica, 2018)
Studies of recent decades have proved the effect on the human body a number of physical factors that are caused by the influence of solar corpuscular streams that change the state of the magnetosphere. The least studied problem is the influence of heliogeophysical factors and solar activity on different periods of organism development, from conception to birth. There is no data on the influence of magnetic storms on spontaneous labor, which was the purpose of this study. Solar activity indicators are presented by the Space Weather Prediction Center (SWPC) of the US National Oceanic and Atmospheric Administration (NOAA: www.swpc.noaa.gov). The results of correlation analysis between spontaneous labor activity of 306 pregnant women in the period of 1.01-08.02.2013 depending on solar activity (Wolf numbers), radio emission flux at the wavelength of 10.7 cm and planetary index (Ap-index) characterizing the physical state of the Earth's magneticfield are analyzed. Reliable correlation between the number of urgent delivery and the flow of radio emission at a wavelength of 10.7 cm and the Wolf numbers was not found. Increase in the activity of spontaneous labor by 2.3 times (r = 0.43; p < 0.05) was recorded three days after the magnetic storm (Ap-index = 21nTl) compared to days calm in geomagnetic terms. The data showed a significant role of dynamics of external factors in the onset of labor.